A neurophysiological and genetic assessment of a case of rapidly progressive scoliosis - Maria Chiara Maccarone; Matilde Paramento; Edoardo Passarotto; Paola Contessa; Maria Rubega; Emanuela Formaggio; Stefano Masiero (European Journal of Translational Myology)
Scoliosis is a three-dimensional spinal deformity characterized by a lateral deviation of at least 10° Cobb, categorized into idiopathic and non-idiopathic forms, caused by identifiable factors like congenital abnormalities, neuromuscular conditions, or genetic syndromes.